HUBUNGAN PENGUASAAN DIKSI DAN TANDA BACA DENGAN KEMAMPUAN MENULIS PERSUASI SISWA KELAS VIII SMPN 10 BANDAR LAMPUNG - Surastina Surastina (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2020)
The problem in this study is to describe the significant relationship between the mastery of diction and punctuation with the ability to write persuasion of grade VIII students in the even semester of State Junior High School 10 Bandarlampung in the 2018/2019 academic year. The method used in this research is correlational. The results of this study are: 1) There is a positive and significant relationship between the mastery of diction and the ability to write persuasion. correlation coefficient = 0.483, while the contribution given by the variable of diction mastery to the ability to write persuasion is 23.329%, then the remaining 76.671% is determined by other variables; 2) There is a positive and significant relationship between the mastery of punctuation and the ability to write persuasion with a correlation coefficient of r = 0.829, while the contribution given by the variable punctuation to the ability to write persuasion is 68.724% and the remaining 31.276% is determined by other variables; 3) There is a positive and significant relationship between the mastery of diction and punctuation with the ability to write persuasion, with a correlation coefficient of R = 0.848, while the contribution given is 71.91% and the remaining 28.09% is determined by other variables / factors.